PERSPEKTIF TENAGA KESEHATAN DALAM PENERAPAN SISTEM INFORMASI MANAJEMEN PUSKESMAS DI KOTA BUKITTINGGI - Utami, Anisa; Ningsih, Ropika; Pebriani, Emi (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Community health centers are the primary healthcare facilities in Indonesia, but many of the services provided are still of poor quality. Service quality can be described by patient waiting times and unintegrated patient data. This is due to inadequate infrastructure to support services. Therefore, the government has issued a policy for community health centers to use a community health center management information system. The purpose of this study is to determine the perspectives of health workers in implementing a community health center management information system. The method used is descriptive qualitative with a centralized interview approach. The participants of this study were 14 health workers taken by purposive sampling. The location of this study was three community health centers in Bukittinggi City, namely the Nilam Sari Community Health Center, the Guguk Panjang Community Health Center, and the Tigo Baleh Community Health Center. This research instrument used an interview sheet and data were collected through semi-structured interviews with data analysis techniques through the use of thematic content analysis. The results of this study are described in two themes: the first theme of the information system facilitating work and improving the quality of services in community health centers and the second theme of obstacles to using the community health center information system consisting of infrastructure constraints such as network and application errors. Thus, it was concluded that the implementation of the community health center information system supported services at the community health center, but there were several obstacles during use, such as network and application errors. Therefore, the researchers hope that this research will be continued with the design of an adequate community health center management information system application by integrating other applications.